JAVASCRIPT LIBRARIES FOR WORKING WITH ARTIFICIAL INTELLIGENCE - J.J. Munirov (Modern World Education: New Age Problems – New solutions, 2025)
This article explores various JavaScript libraries designed for working with artificial intelligence (AI). It examines the underlying technologies, usage areas, and integration methods of these libraries. Additionally, it provides insights into their advantages, challenges, and the future of AI-powered JavaScript development. The article highlights the potential of these libraries in simplifying and accelerating AI tasks for web and mobile applications.